Correlation between shallow benthic zones and calcareous plankton zones at the Bartonian-Priabonian transition: preliminary results from the Varignano section (Trento Province, northern Italy) - PAPAZZONI, Cesare Andrea; Moretti A.; Luciani V.; Fornaciari E.; Giusberti L. (Springer, 2014)
The Varignano section (Trento province, northern Italy), the sediments of which were deposited in a bathyal palaeoenvironment, contains eight resedimented bioclastic levels with larger foraminifera, thus providing an excellent opportunity to directly correlate the shallow benthic zones (SBZs) with the standard calcareous planktonic zones around the Bartonian–Priabonian transition. Moreover, this section is located only 80 km from the Alano di Piave section (Veneto region), a candidate to host the GSSP of the base of Priabonian, where this direct correlation is hampered by the absence of resedimented levels across the critical interval. The preliminary results of the integrated study of calcareous plankton and larger foraminifera reveal that the extinction of morozovellids and large acarininids (E13–E14 boundary) occurs within SBZ18 and not at the SBZ18–SBZ19 boundary as usually considered.